The Application of Intuitionistic Fuzzy Analytic Hierarchy Process (IFAHP) in solving personnel selection problem / Nor Faradilah Mahad ... [et al.] - Mahad, Nor Faradilah; Che Mat Zain, Che Siti Zaiznena; Mohd Syahidan, Saffiya Nuralisa; Saidin, Nur Qamarina Hanim (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Skilled and knowledgeable personnel is the best asset to a company since they play a role in ensuring the business's success. Selecting the best personnel for a particular job position is a crucial process and this decision-making process is part of the Multi-Criteria Decision Making (MCDM) problems since this process involves multiple criteria that are often in conflict. Generally, an interview process is conducted to determine and assess if the candidates have what it takes to fulfil the job's scope. However, in this study, an MCDM method is used to solve the problem. Hence, the decision-makers (DMs) will not depend solely on the traditional method to choose the new personnel. In the study, the Intuitionistic Fuzzy Analytic Hierarchy Process (IFAHP) method is used to solve the personnel selection problem. IFAHP method is an extension of the Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (FAHP) methods. The AHP method is one of the popular MCDM methods and is known for its simplicity. However, the AHP method is often criticised for its inability to handle the uncertainty and vagueness of human judgment (Xu and Liao, 2013). Hence, the FAHP method is introduced to overcome the shortcomings of the AHP method. FAHP method is a combination of Fuzzy set (FS) theory and AHP method. Zadeh (1965) introduced the FS theory to deal with the vagueness of human judgment based on a degree of membership. FS theory resembles human reasoning in its use to approximate information and to deal with uncertainty while making decisions (Kahraman et al., 2004). The FS theory is then extended to the Intuitionistic fuzzy set (IFS) theory introduced by Atanassov (1986). The IFS theory is characterised by a membership function, a non-membership function, and a hesitation function. In IFSs, it is possible to model unknown information while taking advantage of the degree of hesitation and the hesitancy degree of DMs considered when they cannot easily express their preference for an alternative (Vafadarnikjoo et al., 2015). The traditional AHP and FAHP methods are extended to the Intuitionistic fuzzy environment to develop the IFAHP method. In addition, the IFAHP method can handle the ambiguity of expert opinions and increase the accuracy of the assessment (Yu et al., 2018) and provides a more accurate representation of the decision-making process, giving a significant advantage over AHP and FAHP methods (Xu and Liao, 2013).